A DECISION SUPPORT MODEL FOR THE CASH REPLENISHMENT PROCESS IN SOUTH AFRICAN RETAIL BANKING - Adendorff, Susan; Kruger, Paul S (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: A scientifically-based decision-making procedure for determining the amount of cash to be held at a cash point of a retail bank at any time without compromising customer service levels or incurring undue cost was developed. A typical retail bank branch ’s total withdrawal and deposit patterns were investigated. The cost parameters relevant to the cash replenishment process were quantified. Alternate policies were developed to significantly reduce the cost of inventory and the average amount of cash carried. By using the model, it was shown that the cost of carrying cash inventory could be reduced by 13 per cent and the average cash inventory by 52 per cent. AFRIKAANSE OPSOMMING: ’n Wetenskaplik-gefundeerde besluitnemingsprosedure is ontwikkel om te bepaal hoeveel kontant gehou moet word op enige tydstip by ’n kontantvoorsieningspunt van ’n handelsbank sonder om klientediens te kompromitteer of om onnodige koste aan te gaan. ’n Tipiese handelsbanktak se totale onttrekkings- en depositopatrone is ondersoek. Die kosteparameters relevant tot die kontantaanvullingsproses is gekwantifiseer. Alternatiewe beleide is ontwikkel om ’n betekenisvolle voorraadkostevermindering asook ’n vermindering van die gemiddelde hoeveelheid kontant wat gedra word, te behaal. Deur die model te gebruik, is daar getoon dat die voorraaddrakoste met 13 persent en die gemiddeldekontantvoorraad met 52 persent verminder kon word.